Pengaruh financial stability dan ineffective monitoring terhadap kecurangan laporan keuangan pada perusahaan farmasi yang terdaftar di BEI pada tahun 2019-2023 - Budiman, Tyara Regina; Karamoy, Herman; Maradesa, Djeini (Yayasan Widyantara Nawasena Raharja, 2025)
This study examines the influence of financial stability and ineffective monitoring on financial statement fraud in pharmaceutical companies listed on the Indonesia Stock Exchange (IDX) during the 2019–2023 period. Using a quantitative approach with purposive sampling, 35 observations from seven companies were analyzed. Financial stability was measured by asset change (ACHANGE), ineffective monitoring was proxied by the proportion of independent commissioners (BDOUT), and financial statement fraud was assessed using the Beneish M-Score. Multiple regression analysis revealed that financial stability has a positive and significant effect on financial statement fraud, while ineffective monitoring has no significant effect. However, when tested simultaneously, both variables jointly have a significant impact on financial statement fraud, with a coefficient of determination (R²) of 21.9%. These findings support the fraud triangle theory, emphasizing financial pressure as a driver of manipulation, and highlight the importance of strengthening internal monitoring systems to mitigate fraud risk.